Upaya Peningkatan Disiplin Guru Melalui Sistem Reward dan Funishment - Sri Wahyuni (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The implementation of this classroom action research departs from the background of the need for renewal in teaching and learning activities carried out by both teachers and students, especially those aimed at achieving the vision and mission of SMPN 1 Pulo Bandring. The aim of this study ; 1. Efforts to Improve Teacher Discipline through the Reward and Funishment System at SMPN 1 Pulo Bandring, Kab. Asahan TP. 2019/2020; 2. Describe the management of learning by the teacher. The school action research was conducted at SMPN 1 Pulo bandring Kab. Asahan. The subjects of this study were teachers of SMPN 1 Pulo bandring, Kab. Asahan, data were collected through observation, interviews, tests, and study documentation. This school action research was carried out in 2 cycles, consisting of planning, acting, observing and reflecting. Keywords: funishment; teacher discipline; reward. Abstrak: Dilaksanakannya penelitian tindakan kelas ini berangkat dari latar belakang perlunya pembaruan dalam kegiatan belajar mengajar baik yang dilakukan oleh guru maupun oleh siswa khususnya yang bertujuan untuk mencapai visi dan misi SMPN 1 Pulo bandring. Penelitian ini bertujuan ; 1. Upaya Peningkatan Disiplin Guru Melalui Sistem Reward dan Funishment di SMPN 1 Pulo bandring Kab. Asahan TP. 2019/2020; 2. Mendeskripsikan pengelolaan pembelajaran oleh guru. Penelitian tindakan sekolah dilaksanakan di SMPN 1 Pulo bandring Kab. Asahan. Subjek penelitian ini adalah guru SMPN 1 Pulo bandring Kab. Asahan, data dikumpulkan melalui observasi, wawancara, test, dan study dokumentasi. Penelitian tindakan Sekolah ini dilaksanakan dalam 2 siklus, terdiri dari perencanaan, pelaksanaan tindakan, pengamatan dan refleksi. Kata Kunci : disiplin guru; funishment; reward.